Geological map of Jutulsessen (Dronning Maud Land) - Elvevold, Synnøve; Engvik, A K; Hansen, C; Jacobs, J; Meiklejohn, I; Myhre, P I; Rudolph, E (Norsk Polarinstitutt, 2021)
Publication Title: Temakart; 54 Place: Tromsø
Keywords: Dronning Maud Land; geologi; kart

Forskrift om etablering, drift og bruk av jordstasjon for satellitt i Antarktis - Kommunaldepartementet (Lovdata, 2017)
Place: Oslo
Keywords: Dronning Maud Land; jus; kommunikasjon; teknologi

East Antarctica and supercontinent configuration: the Dronning Maud Land perspective - Jacobs, Joachim; Elburg, Marlina; Läufer, Andreas; Jokat, Wilfried (Japan Geoscience Union, 2015)
The geology of East Antarctica and its correlation in major supercontinents is highly speculative, since only a very small part of it is exposed. Therefore a better connection between geology and geophysics is needed in order to correlate exposed regions with ice-covered, geophysically-defined, blocks. In Dronning Maud Land (DML), two distinct late Mesoproterozoic/early Neoproterozoic tectono-metamorphic provinces appear, separated by the major, NE-trending Forster Magnetic Anomaly and South Orvin Shear Zone. To the west of this lineament, the Maud Belt has clear affinities with Grenville-age continent-continent mobile belts. East of the Forster Magnetic Anomaly, juvenile rocks with early Neoproterozoic age (Rayner-age) and an accretionary character crop out. The international GEA-II expedition (2012) targeted a white spot on the geological map immediately to the E of the Forster Magnetic Anomaly. This area allows the characterization and ground-truthing of a large and mostly ice-covered region, the SE DML Province that had previously been interpreted as an older cratonic block. However, new SHRIMP/SIMS zircon analyses and their geochemistry indicates that the exposed basement consists of a ca. 1000-900 Ma juvenile terrane that is very similar to rocks in Sor Rondane. It lacks significant metamorphic overprint at the end of crust formation, but it shows medium to high-grade overprinting between ca. 630-520 Ma, associated with significant felsic melt production, including A-type granitoid magmatism. Therefore, the aeromagnetically distinct SE DML province does neither represent the foreland of a Late Neoproterozoic/EarlyPaleozoic mobile belt, nor a craton, as has previously been speculated. It more likely represents the more juvenile, westward continuation of Rayner-age crust (1000-900 Ma). To the west it abuts along the NE-trending Forster Magnetic Anomaly. The latter is interpreted as a suture, which separates typical Grenville-age crust of the Maud Belt (ca. 1200-1030 Ma) to the W from Rayner-age crust to the E. Therefore the larger eastern part of DML has clearly Indian affinities. Its juvenile character with a lack of metamorphic overprint at the end of crust formation points to an accretionary history along this part of the Indian segment of Rodinia, immediately following final Rodinia assembly.
Publication Title: Japan Geoscience Union meeting Place: Chiba-city, Japan
Keywords: Dronning Maud Land; geofysikk; geologi

Forskrift om miljøvern og sikkerhet i Antarktis - miljødepartementet, Klima- og (Lovdata, 2013)
Volume: 2013-04-26-412 Place: Oslo
Keywords: Antarktis; Dronning Maud Land; forurensning; forvaltning; jus; miljøvern; naturvern

Geological map of Heimefrontfjella, Dronning Maud Land, Antarctica (Scale 1:250,000) - Jacobs, Joachim; Bauer, Wilfried; Kreutzer, Stefan; Patzelt, Gernot; Schmidt, Rainer; Schulze, Peter; Siegesmund, Siegfried; Spaeth, Gerhard; Thomas, Robert J; Weber, Klaus; Zarske, Gerd (PANGAEA, 2009)
The geological overview map was compiled from 15 geological maps (1 : 25,000) and is based on Jacobs et al. 1996. The topographic basemaps were adapted from unpublished 1:250,000 provisional topographic maps, Institut f. Angewandte Geodäsie, Frankfurt, 1983. Part of the contour lines are from Radarsat (Liu et al. 2001).
Keywords: Dronning Maud Land; geologi; kart; topografi

Radar Scattering Zones across Dronning Maud Land, East Antarctica - Müller, Karsten; Albert, Mary; Hamran, Svein Erik; Hagen, Jon Ove Methlie (International Glaciological Society, 2008)
Publication Title: International Symposium on Radioglaciology and its Applications Place: Madrid, Spain
Keywords: Dronning Maud Land; geovitenskap; glasiologi

Kvitkuven: Kronprinsesse Märtha Kyst (Norsk Polarinstitutt, 1997)
Pages: Blad/Sheet B6S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Vestfjella Aust: Maudheimvidda (Norsk Polarinstitutt, 1997)
Pages: Blad/Sheet C7S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Vestfjella Vest: Maudheimvidda (Norsk Polarinstitutt, 1997)
Pages: Blad/Sheet B7S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Ahlmannryggen: Maudheimvidda (Norsk Polarinstitutt, 1996)
Pages: Blad/Sheet G5S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Jutulstraumen: Maudheimvidda (Norsk Polarinstitutt, 1996)
Pages: Blad/Sheet G6S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Nature environment map: Gjelsvikfjella and Western Mühlig-Hofmannfjella, Dronning Maud Land, Antarctica - Høgvard, K (Norsk Polarinstitutt, 1993)
Pages: Blad/Sheet 1 Publication Title: Norsk Polarinstitutt Temakart Nr. 24 Place: Oslo
Keywords: Dronning Maud Land; NARE 1984/85; NARE 1989/90; geografi; kartlegging

Digestibility of krill in crabeater seals and minke whales - Mårtensson, Per-Erik; Nordøy, Erling S; Blix, Arnoldus Schytte (1993)
Pages: 73 Publication Title: 10th Biennial Conference on the Biology of Marine Mammals Place: Galveston, Texas, USA
Keywords: Dronning Maud Land; forskning; hvaler; krill; plankton; seler; zoologi

Satellite tracking of crabeater seals off Queen Maud Land in Antarctica - Nordøy, Erling S; Folkow, Lars P; Blix, Arnoldus Schytte (1993)
Pages: 81 Publication Title: 10th Biennial Conference on the Biology of Marine Mammals Place: Galveston, Texas, USA
Keywords: Dronning Maud Land; satellitt; seler; telemetri; zoologi

Jutulsessen: Fimbulheimen (Norsk Polarinstitutt, 1992)
Place: Oslo
Keywords: Dronning Maud Land; Troll forskningsstasjon; geografi; kartlegging; satellite bilder

H.U. Sverdrupfjella: Fimbulheimen (Norsk Polarinstitutt, 1991)
Pages: Blad H6S Place: [Oslo]
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Jutulgryta: Fimbulheimen (Norsk Polarinstitutt, 1991)
Pages: Blad/Sheet H5S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Mühlig-Hofmannfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1991)
Pages: Blad/Sheet J5S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Mühlig-Hofmannfjella Sør: Fimbulheimen (Norsk Polarinstitutt, 1991)
Pages: Blad/Sheet J6S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Heimfrontfjella Nord: Maudheimvidda (Norsk Polarinstitutt, 1988)
Pages: Blad/Sheet D8 Place: Oslo
Keywords: Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Heimfrontfjella Sør: Maudheimvidda (Norsk Polarinstitutt, 1988)
Pages: Blad/Sheet D9 Place: Oslo
Keywords: Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Development of chicks during extreme cold conditions: the Antarctic Petrel (Thalassoica antarctica) - Bech, Claus; Mehlum, Fridtjof; Haftorn, Svein (University of Ottawa Press, 1988)
Pages: 1447-1456 Publication Title: Acta XIX Congressus Internationalis Ornithologici Volume: 2 Place: Ottawa, Canada
Keywords: Dronning Maud Land; fugler; konferanse; kongress; ornitologi; zoologi

Flichnerfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1984)
Pages: Blad/Sheet K5 Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Norwegian Antarctic Research. Past and Present. - Orheim, Olav (University of Chile, 1977)
Pages: 154-160 Publication Title: El desarrollo de la Antártica Place: Punta Arenas, Chile
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; NARE ekspedisjoner; Weddellhavet; geologi; glasiologi; havis; hvalfangst; kongress; marin biologi; marin geofysikk; marin geologi; meteorologi; oseanografi; symposium

Forposten: Fimbulheimen (Norsk Polarinstitutt, 1975)
Pages: Blad/Sheet N5 Place: Oslo
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Svalbard - Jan Mayen - The Antarctic Possessions (Utenriksdepartementet, 1973)
Publication Title: Norway Information Volume: UDA 297/73 Place: Oslo
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Peter I. Øy; polarområdene

Annandagstoppane. Maudheimvidda (Norsk Polarinstitutt, 1972)
Pages: Blad E6 Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging

Vestfjella Aust: Maudheimvidda (Norsk Polarinstitutt, 1972)
Pages: Blad/Sheet C7 Place: Oslo
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk Antarktisekspedisjon 1968-69; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Vestfjella Vest: Maudheimvidda (Norsk Polarinstitutt, 1972)
Pages: Blad/Sheet B7 Place: Oslo
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk Antarktisekspedisjon 1968-69; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Geology of western Queen Maud Land - Roots, Ernest Frederick (American Geographical Society, 1969)
Pages: Folio 12. Geologic map of Antarctica. Sheet 6 Publication Title: Antarctic Map Folio Series Place: [New York]
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geologi

Kronprinsesse Märtha Kyst - Maudheimvidda: Dronning Maud Land (Norsk Polarinstitutt, 1963)
Place: [Oslo]
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Maudheimvidda Aust: Dronning Maud Land (Norsk Polarinstitutt, 1963)
Place: Oslo
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Borgmassivet: Maudheimvidda (Norsk Polarinstitutt, 1962)
Pages: Blad/Sheet F6 Place: Oslo
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Giæverryggen: Maudheimvidda (Norsk Polarinstitutt, 1962)
Pages: Blad/Sheet F5 Place: Oslo
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Noteveksling mellom Norges regjering og Sør-Afrika-Sambandets regjering angående lån til Sør-Afrika-Sambandet av Norway Station beliggende i det norske biland Dronning Maud Land - Utenriksdepartementet (Statsrådsekretariatet, 1960)
Pages: 197-205 Place: Oslo
Keywords: Dronning Maud Land; jus; politikk; stasjoner

Dronning Maud Land: Sør-Rondane - Luncke, Bernhard (Norsk Polarinstitutt, 1957)
Place: [Oslo]
Keywords: Antarktiske ekspedisjon 1946-47; Dronning Maud Land; Richard Evelyn Byrd; flyfoto; geografi; kartlegging; luftfoto

Sydishavet: Blad 2 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1950)
Place: Sandefjord
Keywords: Bouvetøya; Dronning Maud Land; Sørishavet; geografi; kartlegging

Antarktiske fugler - Holgersen, Holger (Stavanger Museum. Naturhistorisk avdeling, 1949)
Pages: 22 s., ill. Place: Stavanger
Keywords: Antarktis; Dronning Maud Land; fugler; ornitologi; zoologi

Lov om Bouvet-øya, Peter I's øy og Dronning Maud Land m.m. (bilandsloven) (Lovdata, 1930)
Volume: 1930-02-27-3 Place: Oslo
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; jus; lovgivning

Politiske forhold i Antarktis - Giæver, John Schjelderup ([s.n.])
Pages: 24 s. Place: [S.l.]
Keywords: Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; ekspedisjoner; historie; internasjonal politikk; opdagelsesreiser; rett

Dronning Maud Land : proposed Norwegian names - [Marstrander, C.]
Pages: 11 s.
Keywords: Dronning Maud Land; geografi